The Prayer of the Prophets in the Book and the Sunnah - Hammoud , Alaa (Islamic Sciences Journal, 2023)
This research deals with the prayer in the Noble Qur’an and what evidenced verses reported by the prophets, and what has been reported of noble prophetic hadiths that urge closeness to Allah Almighty with help and forgiveness through praising Allah or asking Allah, that spiritual spirit that establishes the goals of the faith in the soul is shown Its meaning and importance through inferring the evidences in which the supplication was mentioned and its great standing, that the worshipper does not call but Allah, for he is the one who is able to ward off calamity and bring benefit to his worshipper , Supplication is called for conditions and desirable things that are desirable when supplicating This is from what was mentioned in the noble Prophet’s Sunnah, and there are times when it is answered, so the Muslim should take advantage of what he desires and the times when the answer is given. All this is from the approach of the Noble Qur’an in impartiality and submission to Allah, and he is the only one who is characterized by oneness and worship, If the worshipper calls to contemplate his Lord, he will extend his hands to him not to return them to zero, either he hastens them in this world or saves them for him in the hereafter, or he may keep him away from a calamity that a person thinks it is good from him